Videotaped Evaluation of Eyedrop Instillation in Glaucoma Patients with Visual Impairment or Moderate to Severe Visual Field Loss - Hennessy, Amy L.; Katz, Joanne; Covert, David; Protzko, Colleen; Robin, Alan L. (Ophthalmology (Rochester, Minn.), 2010)
Objectively evaluate the ability of visually disabled glaucoma patients to successfully administer a single drop onto their eye. Prospective, observational study. Experienced glaucoma patients with Early Treatment of Diabetic Retinopathy Study visual acuity (VA) of ≤6/18 (≤20/60) ≥1 eye, or moderate or severe visual field damage in ≥1 eye. Subjects were “low vision” (20/60 ≤VA <20/200) or “blind” (light perception <VA ≤20/200). They completed a survey about eyedrop use, and were video-recorded instilling 1 drop into their worst-seeing eye in their usual fashion, using a 5-ml bottle. Successful instillation of a single drop. Of 204 glaucoma subjects (55% female; 74% Caucasian; 89% primary open-angle glaucoma; mean age, 68.8±13.1 years), 192/204 (94%) used drops >6 months. Subjects used a mean of 1.9±1.1 bottles of intraocular pressure-lowering medications to treat their glaucoma. Seventy-six percent (155/204) of subjects had severe visual field damage, with a mean deviation of −14.5±8.0. Twenty-six percent (54/204) had acuity of ≤20/200 in ≥1 eye, and subjects had a mean logarithm of minimal angle of resolution acuity of 0.8±0.9. Seventy-one percent of subjects were able to get a drop onto the eye; only 39% instilled 1 drop onto the eye without touching the ocular surface, instilling a mean 1.4±1.0 drops, using 1.2±0.6 attempts. Of the 142 subjects who denied touching the bottle to the ocular surface, 24% did touch the bottle to the eye. Multiple factors were tested for ability to predict successful application of an eyedrop; however, only age (<70 vs ≥70 years) was found to be a significant predictor for less successful instillation. In this video analysis of visually impaired glaucoma patients, we evaluated the difficulty this population has instilling eyedrops, most important, the use of multiple drops per instillation, potential contamination of a chronically used bottle, and poor patient understanding of the situation. Ability to self-administer eyedrops and cost considerations of wasted drops must be thought out before institution of glaucoma therapy. Efforts to determine better methods of eyedrop administration need to be undertaken. Proprietary or commercial disclosure may be found after the references.